The Encyclopedia of religion - ENCYCLOPEDIA... (Macmillan Publishing Company, 1987)
Oen, Jil.1=c.1-2/jil.2=c.1/ Jil.3=c.1-3/Jil.4=c.1/jil.5=c.1-3/Jil.6=c.1/jil.7=c.1-3/Jil.8=c.1/jil.9=c.1-3/Jil.10=c.1/Jil.11=c.1-3/Jil.12=c.10/Jil.13=c.1-3/Jil.14=c.1/Jil.15=c.1-3/Jil.16=c.1/stoc3=31 eks (genap/utuh)/ stc14=jl.11=c.4